Principles of Treating the Sequelae of Perthes Disease - Muhammad Arsalan, Midrarullah Khan, Mauzzmah Shahid, Zeeshan Qamar, Sana Akhlaq, Assad Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Perthes disease is a form of juvenile idiopathic osteonecrosis characterized by temporary bone mortality due to inadequate blood supply to the femoral head. Objectives: This cross-sectional study aimed to evaluate the treatment outcomes and sequelae of Perthes Disease and to identify the most effective treatment modalities for managing its sequelae. Methods: The research enrolled 59 Perthes Disease patients who had completed treatment at our institution between 2021 and 2022. The information pertaining to demographic characteristics, clinical presentations, radiological findings, specific treatments administered, and follow-up records were collected. Pain levels and hip functionality were secondary outcome measures. The Harris Hip Score (HHS) was used to assess the primary outcome of quality of life. Practical Implication: The practical implications for treating the sequelae of Perthes disease include early detection, a multidisciplinary approach, conservative management, surgical interventions when necessary, rehabilitation and physical therapy, long-term monitoring, and patient and family education. Timely diagnosis, collaboration among healthcare professionals, tailored treatment plans, and regular follow-up are important for optimizing outcomes and managing the condition effectively. Results: The average age of the study population was 4.76+1.10 years, with a higher proportion of males. Left-sided (59.32%) participation was more prevalent than right-sided (37.28%) participation (p<0.05). The disease's duration differed between patients. The majority of participants exhibited clinical symptoms such as hip or groin pain, limping, restricted hip movement, and deformities. The most prevalent treatment modality (p<0.05) was physical therapy (52.54%), followed by orthotic devices (30.50%) and surgical interventions (16.94%). Surgical procedures employed both extra-articular (70%) and intra-articular techniques (10%) (p<0.05). Conclusion: Multimodal, patient-specific approach is essential for managing Perthes disease sequelae. Physical therapy was the primary modality of care, while surgical interventions were employed selectively. Significant improvements were observed in pain reduction, functional outcomes, deformity correction, and ROM as a result of the treatment. These findings provided important insights into the management of Perthes disease and highlighted the need for individualized treatment strategies to achieve optimal patient outcomes. Keywords: Harris Hip Score; Perthes Disease; Orthopedic deformities; Orthotic devices; Radiological examination.